Pengaruh Disiplin Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan pada PT Megah Alkesindo Jakarta - Dandy Rio Triananda, (Jurnal Publikasi Ilmu Manajemen, 2025)
Employee Performacnce is one of important aspect for the company, of course the company expects its employees to make a good contribution to the progress of a business. In order to get good employee performance, of course there are many supporting factors, in this case the author focuses on work dicipline and work environment factors. The purpose of this research is to find out whether there is an effect between work dicipline and work environment on employee performance at PT Megah Alkesindo Jakarta. The research method used is Quatitative Statistics, using data collection techniques in the form of observation, interviews and distributing questionnaires to 50 employees at PT Megah Alkesindo Jakarta (Saturated sample technique). The testing methods used are data quality test, classical assumption test, hypothesis of determination test. The result of the test conclude that there is a partial and significant influence between work dicipline on employee performance and between the work environment on employee performance, and simultaneously between work dicipline and work environment on employee performance. Based on the results of the coefficient of determination test, work dicipline and work environment ability to effect the employee performance by 62.8%, while the remaining 37.2% is affected by other factors.